Impact of serum uric acid on incident hypertension in a worksite population of Japanese men. Issue 7 (July 2018) - Kansui, Yasuo; Matsumura, Kiyoshi; Morinaga, Yuki; Inoue, Minako; Kiyohara, Kanako; Ohta, Yuko; Goto, Kenichi; Ohtsubo, Toshio; Ooboshi, Hiroaki; Kitazono, Takanari
Abstract : Objective: Higher levels of serum uric acid are associated with an increased risk of cardiovascular diseases, which may be confounded by comorbidities. We investigated the effects of serum uric acid on the risk of hypertension in Japanese men at a worksite. Methods: We evaluated a total of 2335 Japanese male workers without hypertension who ranged in age from 18 to 64 years at a worksite in 2009. These men were followed for 6 years from 2009 to 2015. Results: During the follow-up period, 380 individuals developed hypertension. The odds ratio for the incident hypertension was estimated according to quartiles of serum uric acid levels of 5.1 or less, 5.2–5.8, 5.9–6.6, and at least 6.7 mg/dl. The multivariable-adjusted risk of incident hypertension was significantly higher in the highest serum uric acid quartile than in the lowest: odds ratio 1.00 (reference) for the lowest quartile, 1.34 (0.91–1.97) for the second quartile, 1.42 (0.97–2.06) for the third quartile, and 1.65 (1.14–2.40) for the highest quartile. In stratified analyses, the association between serum uric acid and incident hypertension was significant in the patients of aged below 45 years and without comorbidities, namely diabetes and low levels of high-density lipoprotein-cholesterol. Conclusions: Serum uric acid levels were associated with the future incidence of hypertension, and the association was observed in the younger individuals, those without diabetes, and those with preserved high-density lipoprotein cholesterol levels in a worksite population of Japanese men. Abstract : Supplemental Digital Content is available in the text